Welfare while working: How does the life satisfaction approach help to explain job search behavior? - Tobias Wolf (Freie Universität Berlin, School of Business & Economics, 2020)
This paper examines the role of life satisfactioninthe labor market behavior of workers receiving welfare benefits while working. Welfare stigma and other hard-to-observe factors may affect outcomes as on-the-job search and the duration until leaving welfare status. We utilize life satisfaction to track such factors. The German PASS-ADIAB dataset combines administrative process data with individual survey data offering a rich database that allows conditioning on changes in household income, time-stable individual traits, employment biographies and local labor market effects.Given a broad set of further covariates, we find that life satisfaction of in-work benefit recipientsis negatively associated with job search, whereas the duration until the exit from welfare is hardly affected. Focusing on heterogeneity among workers suggests that life satisfactions' role for choice depends on the institutional setting, rendering marginally employed workers specifically prone to life satisfaction.
urn:nbn:de:kobv:188-refubium-28128-0
Keywords: J60; J62; I31; I38; 330; life satisfaction; job search; in-work benefits; welfare stigma